Efektivitas Person Centered Therapy Dengan Teknik Katarsis Emosi Dalam Mengatasi Trauma Emosional Akibat Kehilangan Orang Tercinta Pada Remaja: Efektivitas Person Centered Therapy Dengan Teknik Katarsis Emosi Dalam Mengatasi Trauma Emosional Akibat Kehilangan Orang Tercinta Pada Remaja - jana fatul (Universitas Veteran Bangun Nusantara, 2026)
Traumatic experiences arising from the loss of a cherished person represent a significant psychological burden commonly faced by adolescents, yet this issue continues to receive inadequate attention within guidance and counseling services. This study was designed to describe and critically examine the extent to which Person Centered Therapy (PCT) combined with emotional catharsis techniques can assist an 18-year-old adolescent in recovering from emotional trauma caused by losing a beloved family member. A qualitative case study approach was utilized through five traumatic counseling sessions with a cliet coded M-I-N, who was undergoing profound grief following the death of her deeply loved grandfather. The PCT framework developed by Carl Rogers was implemented in an integrated manner alongside emotional catharsis, the empty chair technique, positive visualization, and guided relaxation. Results reveal that this series of counseling interventions successfully encouraged the client to release long-suppressed emotions, facilitated adaptive acceptance of her loss, and enabled the reconstruction of personal meaning and inner resilience. Measurable positive changes began to emerge progressively from the third session onward, as the client demonstrated a growing capacity to express her feelings freely within a safe and supportive environment. This study affirms the critical importance of humanistic, client-centered approaches as effective intervention frameworks for grief-related trauma among adolescents. Keywords: Person Centered Therapy, emotional catharsis, emotional trauma, grief, adolescents